Ideolgy and the De/Naturalization of Meaning in the Cameroonian Novel - Yewah, Emmanuel (Afrika Focus, 1993)
This article shifts the focus of the study of ideology from the question "what is ideology?" to how it is produced and reproduced. It deals with the process by which social subjects/characters, i. e.. the dominant class and the subjugated, participate, through their interactions in the network of relationships, in the production and reproduction of ideologies and meanings once they have become educated, through their experiences and by other social activists, of their subjugating effects. KEY WORDS : (re)production, meaning, text